Effect of pea (Pisum sativum L.) as alternative to soybean meal on the productive performances and meat quality traits of Merino crossbred lamb types - Colonna, Maria Antonietta; Giannico, Francesco; Marsico, Giuseppe; Vonghia, Gino; Ragni, Marco; Caputi Jambrenghi, Anna (Progress in Nutrition, 2014)
The increasing use of genetically modified (GM) feeds has aroused many concerns in Europe. The need to replace such an important protein source like soybean in livestock feedstuffs has led to revalue the use of legume grains such as pea (Pisum sativum), lupin (Lupinus albus) and field bean (Vicia faba var. minor). The use of the these legume grains may lower the European dependence of protein rich feeds. The cultivation of legume grains is economically feasible and is widely practiced in South Italy due to the favorable land and climatic conditions and accordingly to the EU provisions on crop rotation. This study was planned in order to evaluate the influence of a diet containing a variety of pea (Pisum sativum L., var. Corallo) commonly cultivated in South Italy as alternative to a traditional soybean meal based diet on the productive performances and meat quality traits in heavy lambs of two local Merino crossbreeds. The experiment was conducted using two different Merino ethnic groups of 20 male lambs each: “Merinizzata Cavone” (MC) and “Merinizzata Leccese” (ML). All the lambs were raised traditionally with their dams suckling milk until the age of 50 days and then they were weaned using a commercial weaning feed for a week. Lambs of each genetic pool were divided into two homogeneous groups (No. = 10) and fed with one of the two pelletted rations containing: a) soybean meal (SBM) or b) pea (PF). Lambs were slaughtered altogether at the age of 100 days. The results show that pea may be successfully used in lamb diets providing satisfactory results in terms of growth performance and meat quality. The MC ethnic group has shown good results in terms of lamb growth along with meat yield and quality. This genotype deserves additional investigation in order to get further insight on the response of animals to dietary treatments, that is extremely variable in lamb breeds commonly used for meat production in South Italy.